Inovasi Modul Ajar Conversation dan Metode Praktikum untuk Meningkatkan Kemampuan Berbicara Bahasa Inggris pada anak di Dusun Purut Desa Parang - Parayu, Jerryan Vicktor; Aisyah, Mia Basyirotul; Pramana, Mahendra Hakim; Muzakki, Imron; Murad, Ivan Hasan (LP2M Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This community service initiative aims to enhance English speaking skills through an innovative tutoring program (Bimbel) for residents of Dusun Purut, Parang Village. The program began with the development of a conversation-based teaching module and employed a practicum method as its primary approach. Through interactive exercises and simulations of daily conversations, the program was designed to provide a more effective and practical learning experience. The results indicate that the implementation of the teaching module and practicum method significantly improved participants' English speaking abilities. Moreover, the program successfully increased learners' motivation. In conclusion, this Bimbel innovation proves effective in improving English communication skills and can be adopted as a relevant learning model within the context of informal education.